Effects of mindfulness-based interventions on depressive symptoms in patients with substance use disorders: a systematic review and meta-analysis - Reangsing Chuntana; Pusuwun Sasinun; Boonsin Suneerat; Oerther Sarah (Sciendo, 2023)
We examined the effects of mindfulness-based interventions (MBIs) on depressive symptoms in patients with substance use disorders (SUDs) and explored the moderating effects of participant, method, and intervention characteristics.